Nucleotide sequence of cloned rat serum albumin messenger RNA. - Sargent, T D (1981)
The nucleotide sequences of the recombinant DNA inserts of three bacterial plasmid clones containing nearly all of the rat serum albumin mRNA have been determined. A statistical analysis of the nucleotide sequence reveals a pattern of repeated internal homology that confirms the "intragenic triplication" model of albumin evolution.